2022
DOI: 10.47176/mjiri.36.103
|View full text |Cite
|
Sign up to set email alerts
|

GFAP and Neuron Specific Enolase (NSE) in the Serum of Suicide Attempters

Abstract: Background: To determine whether neuronal damage and/or neuroinflammation exist in the brain of suicide attempters and to find a novel biological biomarker to help distinguishing high risk individuals with suicide behavior, we aimed to measure glial fibrillary acidic protein (GFAP), neuron specific enolase (NSE), and nerve growth factor (NGF) in suicide attempters. Methods: In the present case-control study, the serum level of NSE, GFAP, and NGF were measured quantitatively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Additionally, the widespread expression of ACE2, the cellular entry receptor for SARS-CoV2, suggests potential direct infection in various tissues, including the brain, leading to dysregulated peripheral tissue inflammation and neurological complications. These findings support the hypothesis that there is an intricate interplay between hyperinflammation, suicidal risk, and the pathophysiology of COVID-19 [15] and long-Covid [44][45][46] As a further confirmation, a cross-sectional study of American adults revealed significantly higher SI/SB scores in subjects with a previous clinical diagnosis of COVID-19 (n = 39) one year after infection compared to those without, despite a similar history of diagnosed depression and anxiety [47]. Similarly, in a retrospective analysis of electronic health records of 153,848 COVID-19 survivors in the US, SI risk one year after infection was 46% higher in the group that had been affected by SARS-CoV-2 compared to the control group of unaffected patients [21,48].…”
Section: Suicide Risk and Covid-19supporting
confidence: 85%
“…Additionally, the widespread expression of ACE2, the cellular entry receptor for SARS-CoV2, suggests potential direct infection in various tissues, including the brain, leading to dysregulated peripheral tissue inflammation and neurological complications. These findings support the hypothesis that there is an intricate interplay between hyperinflammation, suicidal risk, and the pathophysiology of COVID-19 [15] and long-Covid [44][45][46] As a further confirmation, a cross-sectional study of American adults revealed significantly higher SI/SB scores in subjects with a previous clinical diagnosis of COVID-19 (n = 39) one year after infection compared to those without, despite a similar history of diagnosed depression and anxiety [47]. Similarly, in a retrospective analysis of electronic health records of 153,848 COVID-19 survivors in the US, SI risk one year after infection was 46% higher in the group that had been affected by SARS-CoV-2 compared to the control group of unaffected patients [21,48].…”
Section: Suicide Risk and Covid-19supporting
confidence: 85%
“…Variations in GFAP levels can manifest in response to traumatic injuries, neurodegenerative or neuroinflammatory processes (Bagheri et al, 2015, Abdelhak et al, 2019), neuropathology (Wang and Parpura, 2016), disruption of the blood-brain barrier (Torres-Platas et al, 2016), and brain vascular inflammation. Serum and cerebrospinal fluid NSE elevation is an effective biomarker for neuronal loss and impairment, brain injury, and neuroinflammation (Park et al, 2019, Bagheri et al, 2022, Haque et al, 2018). It is noteworthy that an increase in the release of neuronal biomarkers into the bloodstream (Arslan and Zetterberg, 2023, Negi et al, 2023) through the glymphatic system may result from apoptosis of brain cells (Hablitz and Nedergaard, 2021, Plog et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Serum GFAP has been proposed as a potential marker for monitoring astroglial pathology in MDD (Hol and Pekny, 2015, Al Shweiki et al, 2017, Steinacker et al, 2021). It was believed that NSE and GFAP serve as prognostic indicators for high-risk suicide attempters (Bagheri et al, 2022). Furthermore, elevated CRP levels were found to be strongly correlated with increases in these neuronal and astroglial projection injury biomarkers in MDD (Al-Hakeim et al, 2023a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations